Effects of blended teaching method on mathematics performance of students at primary level: A case of public school of district Dera Ghazi Khan, Punjab, Pakistan - Muhammad Hafeez; Rukhsana Durrani; Aqsa Saleem; Fatima Tahira (Jurnal Cakrawala Pendidikan, 2023)
The objective of this investigation was to assess the effects of blended teaching method on Mathematics performance of 3rd grade learners at primary educational level. A quasi-experimental design of study was formulated to conduct this study. The convenient technique of sampling was employed to collect the required data as one of the researcher was working in the school from which data was collected. The population comprised of 53 3rd grade learners. The sample was separated into two groups. One group named as experimental group (n=28) and other group as a control group (n=25). The pretest and posttest tools were employed to collect the data. The SPSS was employed for the analysis of collected data. The results were significantly different for control and experimental groups in Mathematics performance of students at grade three. The results were supporting blended teaching method that had positive effect on the Mathematics performance for both male and female students of grade three. The effect size was 1.6043 in favor of blended teaching method than that of traditional teaching method. The study also recommended to use the blended teaching method in other science course beside mathematics to find its effectiveness.